2018
DOI: 10.1073/pnas.1811828115
|View full text |Cite
|
Sign up to set email alerts
|

JAZ repressors of metabolic defense promote growth and reproductive fitness in Arabidopsis

Abstract: SignificanceThe plant hormone jasmonate promotes resistance to plant-eating organisms, ranging from pathogenic microbes to mammals. Jasmonate reprograms metabolism to fuel the production of diverse defense compounds and simultaneously inhibits plant growth. Understanding how growth is influenced across a range of defense levels remains unclear, but has important implications for optimizing crop productivity. Using a genetic approach to “tune” the jasmonate response, we assessed the physiological consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
235
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(245 citation statements)
references
References 80 publications
10
235
0
Order By: Relevance
“…Consistent with the notion that AtJAZs perform partially overlapping tasks, analysis of multi-order jaz mutants (i.e., defective in several JAZ genes) revealed that plant sensitivity to JA-Ile gradually increases as more JAZs are removed (Campos et al, 2016;Guo et al, 2018b). Graduated JAZ deficiency in Arabidopsis also increases resistance to biotic stress and concomitantly decreases growth and reproductive output (Guo et al, 2018b). These findings indicate that although AtJAZs are potent repressors of diverse defense responses, they also behave as positive regulators of growth and reproductive fitness.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with the notion that AtJAZs perform partially overlapping tasks, analysis of multi-order jaz mutants (i.e., defective in several JAZ genes) revealed that plant sensitivity to JA-Ile gradually increases as more JAZs are removed (Campos et al, 2016;Guo et al, 2018b). Graduated JAZ deficiency in Arabidopsis also increases resistance to biotic stress and concomitantly decreases growth and reproductive output (Guo et al, 2018b). These findings indicate that although AtJAZs are potent repressors of diverse defense responses, they also behave as positive regulators of growth and reproductive fitness.…”
supporting
confidence: 53%
“…Progress toward this goal, however, has been hampered by genetic redundancy within the JAZ gene family, which in Arabidopsis consists of 13 members (Howe et al, 2018). Consistent with the notion that AtJAZs perform partially overlapping tasks, analysis of multi-order jaz mutants (i.e., defective in several JAZ genes) revealed that plant sensitivity to JA-Ile gradually increases as more JAZs are removed (Campos et al, 2016;Guo et al, 2018b). Graduated JAZ deficiency in Arabidopsis also increases resistance to biotic stress and concomitantly decreases growth and reproductive output (Guo et al, 2018b).…”
mentioning
confidence: 92%
“…The msd1 mutant displayed a large panicle phenotype due to greater size and number of inflorescence branches, suggesting that JA regulates pedicellate spikelet fertility in sorghum (Jiao et al ., ). Arabidopsis mutants defective in JA biosynthesis and signalling pathway, such as dad1 , opr3 , myc2/3/4/5 , and coi1 , displayed a male sterility phenotype caused by delayed anther dehiscence, inactive pollen and short filament elongation (Feys et al ., ; Stintzi & Browse, ; Ishiguro et al ., ; Browse, ; Qi et al ., ) and jazD (defective in 10 JAZ genes) exhibited slow vegetative growth and low fertility, but powerful resistance to necrotrophic pathogens and insect herbivores (Guo et al ., ). In Marchantia polymorpha , Mpjaz showed dwarf phenotypes, narrow branches, and aberrant antheridiophores (Monte et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, MYCs simultaneously target various negative regulators enabling MYCs to efficiently dampen the JA response pattern. Key negative regulators of JA signaling are the JAZ repressors, a gene family of 13 members in Arabidopsi s (Guo et al, 2018, Chung et al, 2010, Cuellar Perez et al, 2014) which can interact with the adaptor protein NINJA to confer TOPLESS-mediated gene repression (Pauwels et al, 2010). Strikingly, all JAZs and also NINJA are directly bound by MYC2 and MYC3 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Uncoupling these subnetworks would be an effective way to determine how they interact to drive very robust activation of the JA pathway. The combination of our multi-omic framework approach coupled with powerful genetic approaches such as the generation of the jaz decuple mutant (Guo et al, 2018) should significantly contribute to a better understanding of JA response pathways…”
Section: Discussionmentioning
confidence: 99%